Gene Flow Risks From Transgenic Herbicide-Tolerant Crops to Their Wild Relatives Can Be Mitigated by Utilizing Alien Chromosomes - Song, Xiaoling; Yan, Jing; Zhang, Yuchi; Li, Hewei; Zheng, Aiqin; Zhang, Qingling; Wang, Jian; Bian, Qing; Shao, Zicheng; Wang, Yu; Qiang, Sheng (Frontiers in Plant Science, 2021)
Integration of a transgene into chromosomes of the C-genomes of oilseed rape (AACC, 2n = 38) may affect their gene flow to wild relatives, particularly Brassica juncea (AABB, 2n = 36). However, no empiric evidence exists in favor of the C-genome as a safer candidate for transformation. In the presence of herbicide selections, the first- to fourth-generation progenies of a B. juncea × glyphosate-tolerant oilseed rape cross [EPSPS gene insertion in the A-genome (Roundup Ready, event RT73)] showed more fitness than a B. juncea × glufosinate-tolerant oilseed rape cross [PAT gene insertion in the C-genome (Liberty Link, event HCN28)]. Karyotyping and fluorescence in situ hybridization–bacterial artificial chromosome (BAC-FISH) analyses showed that crossed progenies from the cultivars with transgenes located on either A- or C- chromosome were mixoploids, and their genomes converged over four generations to 2n = 36 (AABB) and 2n = 37 (AABB + C), respectively. Chromosome pairing of pollen mother cells was more irregular in the progenies from cultivar whose transgene located on C- than on A-chromosome, and the latter lost their C-genome-specific markers faster. Thus, transgene insertion into the different genomes of B. napus affects introgression under herbicide selection. This suggests that gene flow from transgenic crops to wild relatives could be mitigated by breeding transgenic allopolyploid crops, where the transgene is inserted into an alien chromosome.